Change in mitral regurgitation severity impacts survival after transcatheter aortic valve replacement. (1st November 2019) - Feldt, Kari; De Palma, Rodney; Bjursten, Henrik; Petursson, Petur; Nielsen, Niels Erik; Kellerth, Thomas; Jönsson, Anders; Nilsson, Johan; Rück, Andreas; Settergren, Magnus
Abstract: Background: The impact of a change in mitral regurgitation (MR) following TAVR is unknown. We studied the impact of baseline MR and early post-procedural change in MR on survival following TAVR. Methods: The SWEDEHEART registry included all TAVRs performed in Sweden. Patients were dichotomized into no/mild and moderate/severe MR groups. Vital status, echocardiographic data at baseline and within 7 days after TAVR were analyzed. Results: 1712 patients were included. 1404 (82%) had no/mild MR and 308 (18%) had moderate/severe MR. Baseline moderate/severe MR conferred a higher mortality rate at 5-year follow-up (adjusted HR 1.29, CI 1.01–1.65, p = 0.04). Using persistent ≤mild MR as the reference, when moderate/severe MR persisted or if MR worsened from ≤mild at baseline to moderate/severe after TAVR, higher 5-year mortality rates were seen (adjusted HR 1.66, CI 1.17–2.34, p = 0.04; adjusted HR 1.97, CI 1.29–3.00, p = 0.002, respectively). If baseline moderate/severe MR improved to ≤mild after TAVR no excess mortality was seen (HR 1.09, CI 0.75–1.58, p = 0.67). Paravalvular aortic regurgitation (PVL) was inversely associated with MR improvement after TAVR (OR 0.4, 95%: CI 0.17–0.94; p = 0.034). Atrial fibrillation (OR 2.1, 95% CI: 1.27–3.39, p = 0.004), self-expanding valve (OR 3.8, 95% CI: 2.08–7.14, p < 0.0001), and PVL (4.3, 95% CI 2.32–7.78. p < 0.0001) were associated with MR worsening. Conclusions: Moderate/severe baseline MR in patients undergoing TAVR is associated with a mortality increase during 5 years of follow-up. This risk is offset if MR improves to ≤mild, whereas worsening of MR after TAVR is associated with a 2-fold mortality increase. Highlights: Mitral regurgitation increases 5-year mortality in TAVR. Improvement of MR after TAVR neutralizes risk of baseline MR. Worsening mitral regurgitation severity confers highest risk of all cause death. Paravalvular leak related to both MR worsening and absence of MR improvement Self expanding valve prostheses linked to MR worsening after adjusting for PVL